What do the students of the History teaching career think about historical temporality and its teaching? (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2020)
This paper presents advances from the first phase of an investigation that enquiry the conceptions of the students of the History teaching career, about historical temporality and its teaching. Some of the results obtained from the application of a semi-structured questionnaire to students of the Teaching Staff in History of the Universidad Nacional de Córdoba who in 2018 attended the residence and teaching practice are analyze. Besides that, learning experiences of ‘temporality in school’ and in the teaching career; representations of historical time; conceptual mastery of temporal categories, and also conceptions about the challenges and problems of their teaching. Chartier understands that the specificity of the story is the ‘reading of time’. In this sense, temporal thought is a priority objective for a school history that bets on the development of historical thought, as a contribution to the formation of critical, democratic and historically conscious citizenships.
Keywords: historical thought; historical time; social representations; students; teachers training